Effectivity of santoquin and vitamin E suplementation on fat value, fatty acid composition and sensory quality of local duck meat - M, Purba; PP, Ketaren; EB, Laconi; CH, Wijaya (Indonesian Journal of Animal and Veterinary Sciences, 2013)
An experiment was conducted to identify the effectivity of antioxidant supplemented in ration for fat and fatty acid consentration and sensory quality of male local duck meat. Two hundred and eighty day old ducks (dod) reared for ten weeks were allotted to either one of 10 treatments in 4 replications with 7 ducks/replication for each treatment. The treatments were: (R0) basal-diet (RB) without antioxidant (control); (R1) RB+50 ppm santoquin (Sq)+100 IU vitamin E (VE); (R2) RB+50 ppm Sq+200 IU VE; (R3) RB+50 ppm Sq+300 IU VE; (R4) RB+100 ppm Sq+100 IU VE; (R5) RB+100 ppm Sq+200 IU VE; (R6) RB+100 ppm Sq+300 IU VE; (R7) RB+150 ppm Sq+100 IU VE; (R8) RB+150 ppm Sq+200 IU VE; (R9) RB+150 ppm Sq+300 IU VE. The experiment was conducted based on completely randomized design with one of the treatments as a control and the others were with antioxidants supplementations. The variables observed were: fat concentration, fatty acid composition and concentration, as well as sensory quality (off odor intensity and description values) in male duck meat. Result showed that Sq+VE supplementation could reduce fat content in duck meat. R1 and R4 were the best level to reduce fat contents in fresh meat, but in boiled meat R8 and R9 treatment was the best. Total composition and the ratio of unsaturated fatty acids were higher then those of saturated fatty acids. The fatty acid concentrations of linoleat (C18:2) and arakidonat (C20:4) increased parareled with Â the antioxidant supplementations in fresh and boiled duck meat. Sq and VE supplementations significantly decreased (P<0,05) intensity off odor (fishy odor) in fresh or boiled duck meat, and 50 ppm Sq+100 IU VE or 100 ppm Sq+100 IU VE was the best treatment to reduce the intensity off odor (fishy odor)on fresh meat, while 150 ppm Sq+200 IU VE or 150 ppm Sq+300 IU VE was on boiled duck meat. It is concluded that lipid oxidation was effectively protected by Sq+VE supplementations resulted is reduced intensity off odor, while the sensory quality of local duck meat increased. Key Words: Local Duck, Antioxidants, Carcass, Fatty Acids, Off Odor, Sensory